The Possibility of Using Remote Sensing in Studying Pigments of Oak Tree (QUERCUS AEGILOPS) In Pirmus Area - Ahmad, Berivan N.; Ibrahim, Salah Matii (Science Journal of University of Zakho, 2019)
Hyperspectral remote sensing (HRS) is one of the advanced technology which began in the early 1980s. It is one of the most significant breakthroughs in remote sensing. It emerged as a promising technology for studying earth’s surface materials in two ways spectrally & spatially. This technology is developed by breaking a broad band from the visible and infra-red spectrum into hundreds of spectral parts to obtain geochemical information from inaccessible planetary surfaces. The ample spectral information provided by hyperspectral data can identify and distinguish spectrally similar materials that enhance the capability of detecting various ground objects in detail. 28 Oak trees (Quercus aegilops) from the village of pirmus/ Duhok were selected to study the possibility of using hyper spectroscopy in studying chlorophyll a and chlorophyll b (Chla, Chlb). The site of the study has four main slope aspects SWNE (south, west, north and, east), seven trees from each of them were used for collecting leave samples. Two mature and healthy leaves samples were collected from the top of each tree and sealed in polyethylene bags and stored in an ice cooler. Laboratory reflectance spectra were acquired for each leave sample from 350 to 2500 nm by using the Analytical Spectral Device (ASD) spectroradiometer. A 0.25 gm. from each leave was dissolved in ethanol to extract (Chla, Chlb). Then, total chlorophyll (Chl) content was measured at 649 & 665 nm by using the 6705UV/VIS spectrophotometer. Results show that the mean value of the entire Chl was 18.96681 mg/gm. Also, the correlation coefficient (R2) of Chla (at 665nm) and Chlb (at 649nm) show a moderately strong relationship between the variables (73.165, 48.089) alternatively, also the standard errors were close to zero (0.0913355 and 0.0512682). The R2 of Chla for the four slope aspects NESW(North, East, South, and West) were 34.112, 79.805, 94.113 and 82.8547 alternatively. Also, the R2 of Chlb for the same four slope aspects was 49.498, 63.25, 76.99 and 74.34 alternatively. All the results in both bands at least show strong relationships between the variables except for the north slope aspect which shows less R2 values (34.112and 49.498). This is because the sun is facing the south slope along all day hours, while there is no direct light facing the north aspect along the day which is directly related to the zenith angle (at the 36N latitude which is about 76.5 deg.). For this reason, the north slope aspect R2 bias the overall R2 of the 28 trees. The statistical analysis shows that all of the standard error values of Chla and Chlb for the four slope aspects NESW were (0.143789, 0.0685267, 0.0419621,0.100696), (0.0222774, 0.0235722, 0.028614, and 0.0161366) alternatively, which indicates that the predicted values (reflectivity values) are close to the real values (chemical analysis values). From the current results, it is very obvious that the ASD Field Spec 3 spectroradiometer is quite an efficient and un destructive tool that can be used for Quercus Aegilops chlorophyll estimation at 665 and 649 nm. Also, the instrument shows the capability of distinguishing the differences in leaf chlorophyll content among the different slope aspects in both bands.